2017
DOI: 10.1002/jnr.24096
|View full text |Cite
|
Sign up to set email alerts
|

mfat‐1 transgene protects cultured adult neural stem cells against cobalt chloride‐mediated hypoxic injury by activating Nrf2/ARE pathways

Abstract: Ischemic stroke is a devastating neurological disorder and one of the leading causes of death and serious disability in adults. Adult neural stem cell (NSC) replacement therapy is a promising treatment for both structural and functional neurological recovery. However, for the treatment to work, adult NSCs must be protected against hypoxic-ischemic damage in the ischemic penumbra. In the present study, we aimed to investigate the neuroprotective effects of the mfat-1 transgene on cobalt chloride (CoCl 2 )-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 63 publications
2
11
0
Order By: Relevance
“…Without interference from long-term dietary of other bioactive compounds, the transgenic mice proved to be a better model compared with exogenous supplementation. Consistent with our pervious report [26], the n-3 PUFAs in the brains of mfat-1 mice not only contain a higher proportion of DHA, but also contain EPA and DPA that are almost absent in the brain of WT mice, which leading to an increase in the overall n-3/n-6 PUFA ratio. The overall increase in n-3 PUFAs should be better than exogenous supplementation of speci c kind of n-3 PUFAs.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Without interference from long-term dietary of other bioactive compounds, the transgenic mice proved to be a better model compared with exogenous supplementation. Consistent with our pervious report [26], the n-3 PUFAs in the brains of mfat-1 mice not only contain a higher proportion of DHA, but also contain EPA and DPA that are almost absent in the brain of WT mice, which leading to an increase in the overall n-3/n-6 PUFA ratio. The overall increase in n-3 PUFAs should be better than exogenous supplementation of speci c kind of n-3 PUFAs.…”
Section: Discussionsupporting
confidence: 91%
“…The mfat-1 transgenic mice were obtained by prokaryotic microinjection as previous report [26], the coding region of C. elegans fat-1 cDNA was optimized to enhance the expression of fat-1 in mammalian cells. The mfat-1 heterozygotes of C57BL/6J and wild-type (WT) C57BL/6J mice were crossed to produce mfat-1 transgene mice and WT littermates.…”
Section: Animal Models and Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…cobalt chloride triggered nSc apoptosis and caused nSc hypoxic injury (21,22). The signaling pathways involved in nSc apoptosis have been investigated; Mfat-1 transgene protects nScs against cobalt chloride-mediated hypoxic injury by activating nrf2/are signaling pathways (21). The present study demonstrated that MSc-eVs also protected nScs against cobalt chloride-induced nSc apoptosis.…”
Section: Discussionmentioning
confidence: 51%
“…collectively, the results indicated that MSc-eVs possibly reduced apoptosis by modulating the mir-210-3p/aiF/BniP3 signaling pathway. cobalt chloride triggered nSc apoptosis and caused nSc hypoxic injury (21,22). The signaling pathways involved in nSc apoptosis have been investigated; Mfat-1 transgene protects nScs against cobalt chloride-mediated hypoxic injury by activating nrf2/are signaling pathways (21).…”
Section: Discussionmentioning
confidence: 99%